Evaluating prevalence and consequence of residual disease in individuals with psoriasis receiving apremilast treatment: results from a US patient survey - Tina Bhutani; Sayeli Jayade; Sanika Rege; Hannah Penton; Vardhaman Patel; Samaneh Kalirai; Daniel Wolin; Kimberly Boyle; Lauren Seigel (Journal of Dermatological Treatment)
Purpose: This noninterventional, cross-sectional survey estimated the prevalence and consequences of residual disease in apremilast-treated US adults with moderate to severe psoriasis. Materials and Methods: Residual disease was defined as experiencing moderate, severe, or very severe psoriasis over the past week or having ≥3% body surface area affected, despite treatment. Factors associated with residual disease and its effects on flare-ups, humanistic burden, and health care resource utilization (HCRU) were evaluated. Results: Of the 344 apremilast users (mean age, 44.9 years; female, 65.4%), 174 (50.6%) had residual disease. It was more prevalent in Black versus White participants (OR, 4.5; 95% CI, 1.6–12.2), those receiving apremilast for ≥1 versus <1 year (OR, 16.5; 95% CI, 7.9–34.4), those reporting ≥2 versus 0 to 1 flare-ups during the past 3 months (OR, 10.0; 95% CI, 5.0–20.1), and those with ≥4 versus 1 to 3 body regions affected at time of survey (OR, 8.6; 95% CI, 3.8–19.8). Participants with versus without residual disease self-reported more psoriasis flare-ups over the past 3 months (mean, 4.7 vs 0.9; p < .001) and more anxiety (89.7% vs 50.0%; p < .001) and depression (69.0% vs 23.6%; p < .001) over the past 30 days. Conclusion: Generally, participants with versus without residual disease also had significantly more comorbidities and greater HCRU.